Hydrogen production from bioinspired methanol reforming at room temperature. Issue 15 (14th July 2021) - Shen, Yangbin; Xu, Ziwen; Wang, Luqi; Zhan, Yulu
Abstract : Hydrogen is a promising energy carrier because of its high gravimetric energy density and extensive sources. Abstract : Hydrogen is a promising energy carrier because of its high gravimetric energy density and extensive sources. But there are still challenges for hydrogen storage and transportation due to its combustibility and explosibility. In situ methanol reforming is considered feasible and promising for hydrogen storage and production. But conventional methanol reforming is carried out at high temperature, accompanied by methanol cracking and CO production. In this research, we describe a new reaction pathway for hydrogen production from bioinspired methanol reforming near room temperature. Firstly, alcohol dehydrogenase (ADH) and coenzyme I (NAD + ) are employed for methanol dehydrogenation (CH3 OH + NAD + → HCHO + NADH + H + ). The methanol could be oxidized by NAD +, and the oxidation product and reduction product are formaldehyde and reductive coenzyme I (NADH), respectively, during the ADH-assisted methanol dehydrogenation. Then, the ruthenium metal organic frameworks (Ru-MOFs) are prepared. This multifunctional catalyst is highly active for formaldehyde decomposition (HCHO + H2 O → CO2 + 2H2 ) and NADH dehydrogenation (NADH + H + → H2 + NAD + ), apart from its high biocompatibility with ADH. Finally, the hydrogen is successfully produced by the hybrid catalysis of ADH and Ru-MOFs through room temperature methanol reforming. The hydrogen production rate is 50.7 mmol h −1 mol −1 Ru at 25 °C, and is sensitive to the pH and temperature of the solution. The maximum hydrogen production rate is up to 106.4 mmol h −1 mol −1 Ru at 35 °C, pH 7.5. This research will provide us with some new inspiration for room-temperature methanol reforming, as well as catalytic processes involving enzymes.